Synthesis and Characterization of Magnesium Zinc Ferrites As EM Source - Yahya, Noorhana; A. Aziz, Azizuddin; Daud, Hanita; Mohd Zaid, Hasnah; Mohamad Nor Aripin, Ami Salwani; Maarof, Norehan (2008)
Fabrication of Mg1-XZnXFe2O4 (where x=0.2, 0.3, 0.4, and 0.5) was carried out using solid state mixing via conventional technique. Oxides of magnesium, zinc and iron with purity of about 99.9% were mixed with distilled water in a milling machine for 12 hours. They were then filtered and pre-sintered at 1250 C and sintered at 1350oC for 10 hours in air. The phase and the crystal structure of the as-prepared samples were identified using X-ray diffraction analysis (XRD. Hysteresis graph was evaluated using Vibrating Sample Magnetometer (VSM) to get the saturation magnetization (emu/g) and coercivity (G) values. Atomic Force Microstructure (AFM) was used to observe the surface morphology. The X-ray diffraction analysis showed major peak at plane (3 1 1) of the cubic structure for all the ferrites. The largest value of density achieved was 4.69 gcm-3 for 0.5 mole fraction of zinc content. Highest saturation magnetization value (3.652 emu/g) was obtained for the 0.3 mole fraction of zinc content. A strong correlation between the saturation magnetization and zinc content was observed. We speculate that it is due to the Heisenberg super-exchange interaction of magnetic Fe3+ and non-magnetic Zn2+ occupying the octahedral and tetrahedral sites, respectively. The sample was used to induce EM field.